Analysis of the effect of welding sequence and speed on the distortion of ASTM A36 joints by MIG method - Purnama, Dewin; Rizkia, Vika; Garjati, Vina Nanda (Jurnal Polimesin, 2023)
The welding process with the Metal Inert Gas (MIG) method often produces distortions that are detrimental to product quality, one of the factors that affect the characteristics of the welding results is heat input. The heat input provided in the welding process is influenced by arc current, arc voltage, and welding speed, besides that the welding sequence can also affect the distortion of thin plates due to welding on materials such as ASTM A36 plates. The welding process uses welding wire/electrode type AWS ER 70S-6 with a diameter of 1.0 mm, the welding parameters applied are: voltage of 22 Volts, current of 150 Amperes, DC + Current type (DCEP), the shielding gas used is 100% Argon with a flow rate of 15 liters per minute, horizontal welding position (1G), the amount of heat input is differentiated by changing the welding speed and the welding sequence used is the stepping stone method. The results of the study using ANOVA indicate that welding distortion increases with an increase in input heat, the repetition of welding sequences leads to greater distortion due to thermal stress, and the welding sequence and input heat have an influence of 80.4% in reducing distortion.